What CBS Wants: How Groups Can Have (Difficult To Uncover) Beliefs. - Jones, Todd (Philosophical Forum)
Focuses on the question whether a group really believes or desires something over and above what its individual members believe or desire. Account of intentionality; Possibility of group belief; Place of intentional groups in social theory.